Micro-Hardness and Surface Roughness of Bulk-Fill Composite Resin: Effect of Surface Sealant Application and Two Bleaching Regimens - Attia, Reham Mohamad; Sobhy, Eman Mohamed; Essa, Mona El Said Abd El Hameed (European Journal of General Dentistry, 2023)
Objectives The aim of this study was to assess the impact of applying a surface sealant and two bleaching regimens, on the micro-hardness, and surface roughness of bulk-fill composite resinMaterials and Methods One-hundred twenty specimens were prepared with a diameter of 5 mm and thickness of 4 mm using bulk-fill composite. Specimens were subdivided into group 1: (n= 60), in which Fortify surface sealant was used, and group 2 (control): (n= 60), in which specimens were only finished and polished. After applying in-office and at-home bleaching, micro-hardness and surface roughness were measured before and after bleaching. Statistical analysis was performed using Student's t-test and paired test.Results Hardness values of group 1 were lower than values of group 2 before and after bleaching, with different bleaching procedures. Applying surface sealant and different bleaching regimens led to a significant difference of surface roughness (p < 0.001).Conclusion Applying surface sealant decreases both micro-hardness and surface roughness. The bleaching procedures significantly affect the surface roughness, but not the micro-hardness.Clinical Significance Surface sealant can enhance the surface roughness of bulk-fill composite in nonstress bearing area as it reduces the surface micro-hardness.
Keywords: bulk-fill; composite; at-home bleaching; in-office bleaching; micro-hardness; surface roughness; surface sealant